Three essays on the market structure of the banking industry in ASEAN-5 / Habib Hussain Khan - Habib Hussain , Khan (2017)
The study aims to examine the role of bank market structure in relation to bank performance, the transmission of monetary policy and the growth of the manufacturing sectors in five economies – Indonesia, Malaysia, the Philippines, Singapore, and Thailand – from the Association of South East Asian Nations (ASEAN-5). The study is divided into three objectives (essays): (i) the relationship between bank market structure and bank performance with reference to the structure-conduct-performance (SCP) hypothesis; (ii) the role of bank market structure for monetary policy transmission through the banks’ lending channel; (iii) the impact of bank market structure on industrial growth in general and the growth of financially dependent industries in particular. Accordingly, each research objective is represented by a separate essay (research article). The first objective (essay 1) examines the relationship between bank market structure and bank performance by applying a new methodology to the SCP paradigm. The new methodology emphasizes the existence of an indirect relationship between bank market structure and bank performance through bank conduct. The results show that the concentrated banking industries allow banks to earn higher profits partially through anticompetitive conduct by banks. These findings are robust across alternative measures, different time horizons and different concentration levels. The second objective (essay 2) explores the impact of bank market structure on monetary policy transmission through the bank lending channel by applying two structural and two non-structural measures of the market structure. The study also considers the banks’ response to changes in monetary policy stance based on their financial strength (size, liquidity, and capitalization). The results indicate that concentrated banking industries undermine the transmission of monetary policy through the banks’ credit channel. The study also finds that the weakening effect of concentration is stronger for highly capitalized, highly liquid and large-sized banks. These findings are robust in relation to alternative measures of monetary policy indicator and different sample periods. Finally, the third objective (essay 3) identifies the role of bank market structure with regard to the growth of manufacturing industries in general and those dependent on external financing in particular. Applying two structural and two non-structural measures of market structure, the study finds that the bank concentration slows down the growth of manufacturing industries, especially the financially dependent ones. These findings are robust in relation to a number of sensitivity checks including alternative measures of financial dependence, endogeneity considerations and institutional factors such as property rights, quality of accounting standards and bank ownership. The overall conclusion from analyses of three objectives (essays) is that concentrated banking industries allow banks to earn higher profits partially through anticompetitive conduct, reduce the effectiveness of monetary policy transmission through the bank lending channel, and slow down the growth of manufacturing industries, especially the financially dependent ones. Therefore, this study suggests that the consolidation policies must be pursued after careful analysis of their impact on bank performance and other economic activities such as monetary policy transmission, economic growth, and financial stability, etc. In doing so, due consideration must be given to all the aspects of the economy that are potentially influenced by the bank market structure.